Implementation of Augmented Reality to Enhance Alphabet Letter Understanding at Paud Bintang Jonggol - Lestari, Sri; Eldina, Ratih; Sumartha, Divaretta K.; Apipah, Nida (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2024)
Implementing Augmented Reality (AR) in Early Childhood Education (PAUD) promises children an interactive and immersive learning experience. In this study, we evaluate the potential of AR in improving the quality of early childhood education. AR can help PAUD educators create a more engaging learning environment where children can learn through games that support the development of motor skills and conceptual understanding. However, challenges such as access to technology, adequate teacher training, and appropriate curriculum planning need to be addressed. Policy support, comprehensive teacher training, and selecting the proper AR application are critical factors in implementing AR in PAUD. This technology has great potential to change how children learn and better prepare them for the future.